Generalized linear mixed models for the genetic evaluation of binary reproductive traits: a simulation study - Garcia, Diogo Anastácio; Pereira, Idalmo Garcia; Silva, Fabyano Fonseca e; Rosa, Guilherme Jordão de Magalhães; Pires, Aldrin Vieira; Leandro, Roseli Aparecida (Revista Brasileira de Zootecnia, 2011)
The objective of this study was to evaluate the use of probit and logit link functions for the genetic evaluation of early pregnancy using simulated data. The following simulation/analysis structures were constructed: logit/logit, logit/probit, probit/logit, and probit/probit. The percentages of precocious females were 5, 10, 15, 20, 25 and 30% and were adjusted based on a change in the mean of the latent variable. The parametric heritability (h2) was 0.40. Simulation and genetic evaluation were implemented in the R software. Heritability estimates (ĥ2) were compared with h2 using the mean squared error. Pearson correlations between predicted and true breeding values and the percentage of coincidence between true and predicted ranking, considering the 10% of bulls with the highest breeding values (TOP10) were calculated. The mean ĥ2 values were under- and overestimated for all percentages of precocious females when logit/probit and probit/logit models used. In addition, the mean squared errors of these models were high when compared with those obtained with the probit/probit and logit/logit models. Considering ĥ2, probit/probit and logit/logit were also superior to logit/probit and probit/logit, providing values close to the parametric heritability. Logit/probit and probit/logit presented low Pearson correlations, whereas the correlations obtained with probit/probit and logit/logit ranged from moderate to high. With respect to the TOP10 bulls, logit/probit and probit/logit presented much lower percentages than probit/probit and logit/logit. The genetic parameter estimates and predictions of breeding values of the animals obtained with the logit/logit and probit/probit models were similar. In contrast, the results obtained with probit/logit and logit/probit were not satisfactory. There is need to compare the estimation and prediction ability of logit and probit link functions.
Keywords: Beef cattle; Early pregnancy; Genetic parameters; GLMM; Link function